Budaya Unik “Munggahan” Menjelang Bulan Ramadhan Di Kabupaten Subang Jawa Barat : Studi Antropologi Al-Qur’an - Alam Tarlam; N. Fitri Amaliya; Ernawati Ernawati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
This research examines the development of the Munggahan tradition in the Subang region of West Java. Munggahan is a tradition of welcoming the month of Ramadan that reflects the values of gratitude and gotong royong in Sundanese society. The research method used is a descriptive qualitative approach, involving field observations, literature studies, and interviews. The results showed that the Munggahan tradition includes several processions such as grave pilgrimage, padusan (holy bathing), eating together, and sidekah (tahlilan). The spiritual and social meanings contained in this tradition include expressions of gratitude to Allah SWT, respect for ancestors, and strengthening social ties within the community. However, research has also revealed a decline in interest in this tradition, especially among the younger generation, due to the influence of Westernization and technological developments. Nevertheless, the values contained in the Munggahan tradition are still considered relevant in the context of modern life, especially in strengthening social solidarity and the cultural identity of Sundanese society. This study concludes that despite the challenges of modernization, the Munggahan tradition still has cultural and spiritual significance for the people of Subang, West Java.